Skin care with Fisha: new media content creation for basic skincare education / Nurain Nafisha Nor Mohd Dini and Ahmad Harith Syah Md Yusuf - Nor Mohd Dini, Nurain Nafisha; Md Yusuf, Ahmad Harith Syah (Academy of Language Studies, 2023)
Skincare information can also be given by developing content linked to the information to be conveyed, prompting this initiative to develop new media content emphasising skincare in the form of material produced on new media platforms. Living in a modernisation era where everyone believes that technology is a good and convenient way to get information that they want to know or seek, this content creation is being made as one of the ways to spread basic information about skincare to the targeted audience through new media content. Viewers can watch and share videos that transmit information using the content creation approach if they believe the content is highly useful and valuable to others. The particular methods of researching, filming, editing, releasing, disseminating the content, and finishing the product's end were required when creating ‘Skin Care with Fisha’ content. Thus, the content creation that has been developed intends to produce available new media material on a new media platform by generating new media content and utilising communication and editing skills.